Fusion of MR and SPECT Images Using Statistics based Guided Image Filter with Weighted Average Rule (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A fast and effective image fusion method is proposed for creating a highly informative fused imagethrough merging multiple images. The proposed method is based on a two-scale decomposition of animage into a base layer containing large scale variations in intensity, and a detail layer capturing smallscale details. A novel Statistics based guided image filtering-based weighted average technique isproposed to make full use of spatial consistency for fusion of the base and detail layers. Experimentalresults demonstrate that the proposed method can obtain state-of-the-art performance for fusion ofmultispectral, multi focus, multimodal, and multi exposure images.